STRATEGI GURU AKIDAH AKHLAK DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SISWA DI MTs NAHDLATUL ULAMA’ NGANTANG - Lutvi Martha Ayunda; Mohammad Afifulloh; Indhra Mustofha (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The strategy of the teacher of moral aqidah in improving student learning discipline is one of the teacher's efforts towards students in educating students' learning discipline attitudes at MTsNU Ngantang school. The purpose of this study was to describe the condition of student learning discipline at MTs Nahdlatul Ulama' Ngantang, to describe the strategy of Akidah Akhlak teachers in improving student discipline at MTs Nahdlatul Ulama' Ngantang, to find out the obstacles of Akidah Akhlak teachers in improving student learning discipline at MTs Nahdlatul Ulama' Ngantang. The results of this study are (1) the condition of student learning discipline is reduced student interest in learning and the application of student sanctions in class. (2) the teacher's strategy of moral aqidah in improving student learning discipline at MTsNU Ngantang such as time discipline, enforcing rules, attitudes, and discipline in worship as well as reinforced by cooperative, affective and expository learning strategies by the teacher to students. (3) From the results of the research, researchers related to the obstacles of teachers' morals in improving student learning discipline as follows: students make noise in class and students are allowed to leave class without proper reasons. Kata Kunci: Strategy, Moral Creed Teacher, Student Learning Discipline